2001
DOI: 10.1002/jctb.461
|View full text |Cite
|
Sign up to set email alerts
|

Styrene degradation along the bed height of perlite biofilter

Abstract: The whole bed height of a bio®lter was divided into four individual reactor stages in series. This con®guration permits a measurement of the leachate pH of each stage individually and minimizes interstage mixing of the immobilized culture. The extent to which the residence time of pollutant in the ®lter bed in¯uenced biodegradation characteristics and the composition of immobilized culture under conditions of a constant loading rate was studied using a perlite bio®lter having an internal diameter of 50 mm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…Changes of the residence time and the C in of styrene thus had very little effect on the overall performance characteristics. This system stability was not just a consequence of the high sorption capacity of the GAC used as packing; the loading at EBRT of 15 with those in this study, it is evident that the activated carbon enabled high and stable EC values at REs above 90% regardless of the pollutant contact time in the reactor bed. The positive effect of the packing material (GAC) on degradation parameters and performance under fluctuating concentration has already been described for toluene, 16 -18 methyl ethyl ketone, 19 and odors and solvents.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Changes of the residence time and the C in of styrene thus had very little effect on the overall performance characteristics. This system stability was not just a consequence of the high sorption capacity of the GAC used as packing; the loading at EBRT of 15 with those in this study, it is evident that the activated carbon enabled high and stable EC values at REs above 90% regardless of the pollutant contact time in the reactor bed. The positive effect of the packing material (GAC) on degradation parameters and performance under fluctuating concentration has already been described for toluene, 16 -18 methyl ethyl ketone, 19 and odors and solvents.…”
Section: Resultssupporting
confidence: 64%
“…A comparison with our previous results 15 achieved in the same reactor configuration using perlite as a packing instead of GAC is not possible because of a much shorter time of experiments (shorter time interval necessary for an achievement of the steady states among the rates of adsorption, desorption, and biodegradation) and also a much lower OL of 140 g C ⅐ m Ϫ3 hr Ϫ1 . Dividing the bed height into several sections permitted not only measurement of pollutant removal in each section but also other characteristics.…”
Section: Degradation Along the Bed Heightmentioning
confidence: 90%
“…Most commercial applications before 1990, however, were for the control of odors [6,7]. In the past decades, many studies have shown that biofiltration can be applied successfully to control or eliminate VOCs [8][9][10][11][12][13][14]. Song et al reported that the microbial response and elimination capacity in biofilters are subjected to high toluene loadings [15].…”
Section: Introductionmentioning
confidence: 99%
“…Styrene is a widely produced aromatic hydrocarbon that is mainly used in the chemical sector for the production of polystyrene, styrene copolymers and polyester resins [1].…”
Section: Introductionmentioning
confidence: 99%